Cytotoxic Amides from Fruits of Kawakawa, Macropiper excelsum - Lei, Jeremy; Burgess, Elaine J.; Richardson, Alistair T. B.; Hawkins, Bill C.; Baird, Sarah K.; Smallfield, Bruce M.; van Klink, John W.; Perry, Nigel B. (Planta Medica, 2015)
Cytotoxic amides have been isolated from the fruits of the endemic New Zealand medicinal plant kawakawa, Macropiper excelsum (Piperaceae). The main amide was piperchabamide A and this is the first report of this rare compound outside the genus Piper. Eleven other amides were purified including two new compounds with the unusual 3,4-dihydro-1(2H)-pyridinyl group. The new compounds were fully characterized by 2D NMR spectroscopy, which showed a slow exchange between two rotamers about the amide bond, and they were chemically synthesized. In view of the antitumor activity of the related piperlongumine, all of these amides plus four synthetic analogs were tested for cytotoxicity. The most active was the piperine homolog piperdardine, with an IC50 of 14 µM against HT 29 colon cancer cells.
Keywords: amides; Macropiper excelsum; Piperaceae; cytotoxicity; synthesis